2011
DOI: 10.1590/s1807-59322011000700018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of an entero-omentectomy in mildly obese type 2 diabetes mellitus patients after three years

Abstract: BACKGROUND:Various digestive tract procedures effectively improve metabolic syndrome, especially the control of type 2 diabetes mellitus. Very good metabolic results have been shown with vertical gastrectomy and entero-omentectomy; however, the metabolic effects of an isolated entero-omentectomy have not been previously studied.METHODS: Nine patients with type 2 diabetes mellitus and a body mass index ranging from 29 to 34.8 kg/m2 underwent an entero-omentectomy procedure that consisted of an enterectomy of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Because visceral adiposity is a risk factor for the metabolic complications associated with obesity, omentectomy was an early proposed surgical intervention to influence type 2 diabetes. Study reports of omentectomy alone, or in addition to a standard bariatric operation, varied as to no benefit (69,70), possible benefit (71,72), and demonstrable benefit (73,74).…”
Section: Nonbariatric Metabolic Surgery For Diabetesmentioning
confidence: 99%
“…Because visceral adiposity is a risk factor for the metabolic complications associated with obesity, omentectomy was an early proposed surgical intervention to influence type 2 diabetes. Study reports of omentectomy alone, or in addition to a standard bariatric operation, varied as to no benefit (69,70), possible benefit (71,72), and demonstrable benefit (73,74).…”
Section: Nonbariatric Metabolic Surgery For Diabetesmentioning
confidence: 99%
“…More specifically, intra-abdominal lipectomy reverses insulin resistance and glucose intolerance in obese, aged and young rodents 76 - 81 . Though controversial in humans, 82 , 83 omental fat removal improves insulin action, 84 , 85 whereas removal of non-visceral fat has no effect 86 . Conflicting results among human omentectomy studies likely occur because outcome measurements are not consistent or sensitive enough to detect metabolic improvements.…”
Section: Identifying the Link Between Visceral Fat And Deleterious Mementioning
confidence: 99%
“…These same authors also found the beneficial effects of the entero-omentectomy alone on the glycemic profile of patients with T2D and obesity degree I during a 3-year follow-up period [23]. Heap et al also presented favorable results regarding the improvement of co-morbidities associated to obesity when performing a technique similar to the Santoro group, which included a subtotal lateral gastrectomy, placement of a gastric ring, partial resection of the jejunum, and omentectomy [24].…”
Section: Fig 3 Preoperative and Presacrifice Insulin Sensitivity Tementioning
confidence: 91%